Outcomes of Kidney Transplantation by Laparoscopic Surgery versus Open Surgery. (July 2018) - He, Bulang; Musk, Gabrielle; Ng, Zi Qin; Newman, Mark; Mou, Lingjun; Mak, Jackie; Tan, Daren; Sinniah, R; Hamdorf, Jeffrey
Abstract : Introduction: Laparoscopic surgery for live donor nephrectomy has become the standard of care due to multiple benefits. This has also facilitated an increase in the live donor pool. Over last few years, laparoscopic surgery for kidney transplantation has been explored with promising results. However, concerns have been raised as to whether there is any additional predisposition to damage to the kidney graft due to prolonged time for vessel anastomosis during learning period. Therefore, the aims of this study are to investigate the outcomes of kidney transplantation by laparoscopic surgery in comparison with open surgery in a large animal model. Materials and Methods: The study was approved by the Animal Ethics Committee of the institute. Eleven large white female pigs, weighing about 40 kg were selected for this study. The model of orthotopic auto transplantation was employed in this study with transplantation performed by laparoscopic surgery in six pigs (LG), and open surgery in five pigs (OG). The technique of laparoscopic kidney transplantation has been described previously with 5 ports and a small ventral midline incision (6-8 cm). The open surgery was performed by a large flank incision about 18 cm in length. The pigs recovered from surgery and were monitored for 4 weeks. Body temperature was monitoredKidney graft temperature was monitored during vessel anastomosis. A kidney biopsy was taken prior to kidney procurement and kidney implantation, immediately post implantation and at the end of study. The time for vessel anastomoses was recordedBlood tests of haemoglobin (Hb) and creatinine (Cr) were done for assessment of the kidney function. Outcomes: All surgeries were performed successfully. The recovery in 7 pigs was uneventful, while 2 pigs in each group required early euthanasia during the recovery period. The venous anastomotic time was similar in both groups, although the renal artery anastomosis was longer in LG (P<0.05). Body temperature was stable during the surgery.Kidney temperature rapidly increased to ~20°C and then slowly increased until completion of vessel anastomosis.The Hb level was stable pre and post surgery in both groups. The peak Cr level was on day 1 and returned to pre-operative levels by day 7. The Cr level was significantly higher in OG on day 1 and day 3 post-transplant, then returned close to normal level from day 7 and remained stable until the end of study. Histopathology of the biopsy was similar in both groups with very mild change. The incision was significantly smaller in LG than OG Conclusion: The recovery of kidney graft function after transplantation was comparable between the two groups.The Kidney graft temperature increased rapidly, then remained steady.There is no specific damage seen on histopathology in the kidney graft that was transplanted by laparoscopic surgery. The major advantage of laparoscopic surgery over open surgery is a minimally invasive with a smaller incision. RAC Grant-Sir Charles Gairdner Hospital 2016/2017. Animal care service & Large animal facility, The University of Western Australia (UWA) for providing the care to the animals. Clinical Training & Evaluation Centre (CTEC), The University of Western Australia, for supporting the equipment. COVIDIEN, B BRAUN, STORZ & APPLIED MEDICAL for generously supplying surgical equipment and instruments.